Randomized controlled trial of erdosteine for acute cough in children with colds - Yenny Yenny; Roni Naning; Amalia Setyati (Paediatrica Indonesiana, 2011)
Background T h e prevalence of the common cold in children is high, v.ith 30% of cases exhibiting an acute cough, the most common complaint by parents. Erdosteine, a recently developed cough medicine, is available for children. Erdosteine has been reported to increase mucodliary clearance, act as an antioxidant and prevent bacterial adhesion.Objective To assess the clinical improvement in acute cough in children \\lith a common cold taking erdosteine vs. a placebo.Methods We conducted a doubleô€€¾blind, randomized, controlled trial at the Public Health Center of Gedongtengen, Yogyakarta with 140 children selected by a consecutive sampling method. Research subjects were randomized by computer program into two treatment groups, those receiving erdosteine therapy and those receiving a placebo. Both groups were monitored for 6 days. A scoring system was used to assess the improvement of acute cough symptoms and analyzed by Chi-square test.Results No significant differences in basic characteristics, cough severity, or environment were found among the 140 children with common cold in the two groups. After 6 days of treatment, no significant difference in clinical improvement of acute cough was found between the erdosteine (65 subjects improved out of 70) and placebo groups (62/70),92.5% and 88.6%, respectively (P=0.382).Conclusion Erdosteine was not more effective than the placebo for treatment of acute cough in children with common cold.